Axial cyclic loading of piles in low-to-medium-density chalk - Buckley, RM; Jardine, RJ; Kontoe, S; Liu, T; Byrne, BW; McAdam, RA; Schranz, F; Vinck, K (ICE Publishing, 2023)
Comprehensive field investigations into the axial cyclic loading behaviour of open steel pipe piles driven and aged in low-to-medium-density chalk identify the conditions under which behaviour is stable, unstable or metastable. Post-cycling monotonic tests confirmed that stable cycling enhanced pile capacity marginally, while unstable cases suffered potentially large losses of shaft capacity. Metastable conditions led to intermediate outcomes. The patterns by which axial deflections grew under cyclic loading varied systematically with the normalised loading parameters and could be captured by simple fitting expressions. Cyclic stiffnesses also varied with loading conditions, with the highest operational shear stiffnesses falling far below the in situ seismic test values. The monotonic and cyclic axial responses of the test piles were controlled by the behaviour of, and conditions within, the reconsolidated, de-structured, chalk putty annuli formed around pile shafts during driving. Fibre-optic strain gauges identified progressive failure from the pile tip upwards. Large factors of safety were required for piles to survive repetitive loading under high-level, two-way conditions involving low mean loads, while low-amplitude one-way cycling had little impact. A simple ‘global’ prediction procedure employing interface shear and cyclic triaxial tests is shown to provide broadly representative predictions for field behaviour.